Loading deproteinized bovine bone with strontium enhances bone regeneration in rat calvarial critical size defects - Aroni, Maurício Andrés Tinajero (2019)
Objective: To evaluate the effect of grafting with strontium (Sr)-loaded deproteinized bovine bone (DBB) on bone healing in calvarial critical size defects (CSD) in rats. Material and methods: Two circular bone defects (5 mm in diameter) were created in the calvaria of 42 rats. One of the defects, randomly chosen, was grafted with (a) DBB, (b) DBB loaded with 19.6 μg/g of Sr (DBB/Sr1), or (c) DBB loaded with 98.1 μg/g of Sr (DBB/Sr2). The other defect was left empty as negative control. Groups of seven animals from each of the groups were euthanized 15 and 60 days post-op. Bone healing in the CSD was evaluated by micro-CT and histology/histomorphometry and immunohistochemistry. Results: DBB/Sr2-grafted sites showed statistically significantly shorter radiographic residual defect length compared with DBB/Sr1- and DBB-grafted sites, and with empty controls at 60 days. Further, the amount of new bone formation in the DBB/Sr1- and DBB/Sr2-grafted sites was significantly higher compared with that in the DBB-grafted sites at 60 days. A larger number of DBB/Sr1- and DBB/Sr2-grafted sites presented with no- or only limited to mild inflammation, compared with the DBB-grafted sites, especially at 60 days. Higher expression of osteocalcin was observed in DBB/Sr1- and DBB/Sr2-grafted sites as compared to DBB-grafted sites. Conclusion: Grafting with Sr-loaded DBB enhanced bone formation in CSD in rats, when compared with grafting with non-loaded DBB. Clinical relevance: Grafting with Sr-loaded DBB may enhance bone formation in bone defects.